The Emerald handbook of wellbeing in higher education : global perspectives on students, faculty, leaders, and institutions - Walker, Keith D.; Kutsyuruba, Benjamin (Emerald Publishing Limited, 2024)
There has been an increased focus on the need to address the wellbeing and mental health challenges that affect humans across organizational settings, including the higher education sector. This comprehensive Handbook is organized into three sections: student wellbeing, faculty and leader wellbeing, and wellbeing initiatives at institutional or systems-level. Scholars from around the globe discuss initiatives, practices, and structures that provide a positive outlook on individual and organizational flourishing in higher learning and offer lessons from efforts to promote positive emotional and social aspects for students, leaders, and faculty. Topics include student resilience and leadership, supervisory relationships, appreciative mentoring, student thriving, issues of mental and physical health, faculty and leader wellbeing, development of wellbeing interventions and health promotion frameworks, and international student wellbeing. The interventions and experiences presented in The Emerald Handbook of Wellbeing in Higher Education are aimed at enhancing flourishing among students, faculty and staff, and across institutions. This Handbook will be helpful to higher education leaders and managers as they consider ways to promote and implement wellbeing strategies within their institutions, whilst encouraging all readers to adopt an appreciative, strengths-based, positive approach to teaching, learning, and leading in higher education contexts.